2021
DOI: 10.1002/edn3.222
|View full text |Cite
|
Sign up to set email alerts
|

High‐throughput identification of non‐marine Ostracoda from the Tibetan Plateau: Evaluating the success of various primers on sedimentary DNA samples

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 81 publications
(124 reference statements)
0
3
0
Order By: Relevance
“…Out of all master mixes screened and validated in this study, the Platinum Direct PCR Universal Master Mix generated reproducible results for all samples tested in this study. In the past, the Platinum Direct PCR Universal Master Mix kit has been used by researchers for the isolation of DNA from seafood specimens (i.e., ostracode) and subsequent PCR amplification ( Echeverría-Galindo et al, 2021 ). This master mix is designed to facilitate PCR amplification directly from tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…Out of all master mixes screened and validated in this study, the Platinum Direct PCR Universal Master Mix generated reproducible results for all samples tested in this study. In the past, the Platinum Direct PCR Universal Master Mix kit has been used by researchers for the isolation of DNA from seafood specimens (i.e., ostracode) and subsequent PCR amplification ( Echeverría-Galindo et al, 2021 ). This master mix is designed to facilitate PCR amplification directly from tissue samples.…”
Section: Discussionmentioning
confidence: 99%
“…With the development of next-generation sequencing technologies (Glenn, 2011;Metzker, 2010;Shendure and Ji, 2008), metabarcoding has shown a great potential for reconstructing long-term changes in different biological groups. Several sets of universal PCR primers suitable for sedaDNA studies have been designed for plants (Taberlet et al, 2007), mammals (Giguet-Covex et al, 2014), fish (Miya et al, 2015), fungi (Seeber et al, 2022), diatoms (Stoof-Leichsenring et al, 2012), ostracods (Echeverría-Galindo et al, 2021), and bacteria (Belle and Parent, 2019). Metabarcodes amplified by these primers offer the opportunity to identify the target groups at high taxonomic levels (e.g., species level), and the bias in taxonomic resolution between different taxa can be further complemented by specific primers.…”
Section: Methodological Opportunities and Limitations Of Sedadna Appr...mentioning
confidence: 99%
“…A recent study about plant DNA preservation in the sediments suggested that lakes with pH 7-9 and conductivities with 100-500 μS/cm may have better preservation of sedimentary DNA compared to lakes with higher or lower values of latter measures (Jia et al, 2021). However, sedimentary DNA studies to identify diatom (Kang et al, 2021) and ostracod (Echeverría-Galindo et al, 2021) communities indicated the potential of DNA metabarcoding in the environmental settings of the lake Nam Co with conductivity >1,400 μS/cm and pH ~9. Although the overall diatom community patterns matched well between morphological and DNA-based identification methods in the study by Kang et al (2021), it also indicated that the diatom species with fragile valves may be missed via microscopical analyses due to the dissolution effect.…”
Section: Introductionmentioning
confidence: 99%